The kill order - Dashner, James, 1972- (New York : Delacorte Press, 2012)
Mark and Trina struggle to survive as modern civilization is destoryed by sun flares and mutating diseases.
Prequel to: The maze runner.
Young Adult.
Young Adult
Keywords: Natural disasters -- Juvenile fiction; Survival -- Juvenile fiction; Virus diseases -- Juvenile fiction; Natural disasters -- Fiction; Science fiction; Survival -- Fiction; Virus diseases -- Fiction; JUVENILE FICTION / Action & Adventure / General; Natural disasters -- Fiction; Science fiction; Survival skills -- Fiction; Viruses -- Fiction; Science fiction